ON FRACTIONAL KdV-BURGERS AND POTENTIAL KdV EQUATIONS Existence and Uniqueness Results - Hashemi, Mir Sajjad; İnç, Mustafa; Baleanu, Dumitru (Vinca Inst Nuclear Sci, 2019)
Recently a new kind of derivatives, namely the conformable derivative is introduced which have not many drawbacks of other fractional derivatives. Two types of KdV equations with conformable derivative are investigated in this paper. Existence and uniqueness of two different equations of KdV class with conformable derivatives are investigated. It is also shown that the invariant subspace method can be extended to find the exact solutions of these equations.
Keywords: conformable fractional derivative; existence and uniqueness; invariant subspace method; KdV-Burgers equation; potential KdV equation